Ultrasonographic Evaluation of the Hypospadiac Penis in Children - Abbas, Tariq O. (Frontiers in Pediatrics, 2022)
Introduction: Identifying key anatomical features of the hypospadiac penis is crucial to better understanding this pathology and guiding surgical reconstruction plans, thereby achieving superior functional and cosmetic outcomes. Objective: Assess feasibility and precision of penile ultrasonography (PUG) in determining key structural features for hypospadias cases (including distal extent of the spongiosal component of the urethral plate, to elucidate the healing process following TIP urethroplasty). Patients and methods: Twenty-five children with hypospadias were assessed using PUG prior to surgical repair and then again under general anesthesia. Preoperative images were acquired using 6 MHz ultrasonography in sagittal and transverse planes, then later compared with anatomical findings obtained during surgical repair of urethral hypoplasia. Results: Median patient age was 1.2 years (range 0.5-12) and hypospadias types included coronal 17/25 (68%), mid-penile 5/25 (20%) and proximal penile 3/25 (12%). Distinct layers of the corpus spongiosa and mucosal layer, Buck fascia, tunica albuginea, glans, corpora cavernosa, and penile skin were delineated so that their spatial inter-relationship could be assessed. Distal extent of the spongiosal component of the urethral wall was determined by the mid-glans B-B line. The extent of urethral hypoplasia identified by PUG was similar to measurements obtained intraoperatively (overall accuracy 92%, 98%, 99% for proximal, mid, and distal hypospadias, respectively). Conclusion: PUG is a feasible and accurate approach to evaluating penile configuration in children with hypospadias. Distal extent of the spongiosal component of the urethral plate was accurately determined, hence PUG could potentially be used to improve surgical planning and appraisal of current repair procedures.